Demand projections for poultry products and poultry feeds in Bangladesh - Islam, K. M. Nabiul (International Food Policy Research Institute, 2003)
The poultry sub-sector is crucially important in the context of agricultural growth and improvement of diets of people in Bangladesh. The sub-sector is particularly important in that it is a significant source for the supply of protein and nutrition in a household's nutritional intake. It is an attractive economic activity as well, especially to women and poor population...[T]he major objective of this study is to carry out demand projections for poultry and poultry products, and thus address the potential of the grain (maize, in particular) economy, through carrying out demand projections for poultry feeds in Bangladesh. More specifically, the study aims to estimate the total use of feed as grain by the poultry sub-sector, through assessing the current levels of demand and supply of poultry and poultry products. -- from Author's Introduction.